Os Investimentos Brasileiros na África no Governo Lula - Júlia Covre Vilas-Bôas (Meridiano 47, 2017)
During Lula’s government Brazilian investments in Africa grew prominently. The main destinations were South Africa, Angola, Libya and Mozambique.